1990
DOI: 10.1038/bjc.1990.266
|View full text |Cite
|
Sign up to set email alerts
|

The use of vascularised spheroids to investigate the action of flavone acetic acid on tumour blood vessels

Abstract: Summary EMT6 multicellular spheroids were introduced into the peritoneal cavities of mice and allowed to become vascularised, resulting in solid spherical tumours. The necrotic cores of the initially avascular spheroids were replaced by vascularised tumour tissue but the outer zones of the spheroids failed to become vascularised. The presence of both vascular and avascular components in each spheroid allowed the role of the vasculature in the antitumour action of flavone acetic acid (FAA) to be determined. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In support of the latter view, growth inhibition of murine colon tumours (but not antivascular effects) is compromised by T-cell depletion (Pratesi et al, 1990;Bibby et al, 1991) although similar studies by Ching et al (1992) showed little loss of activity of either FAA or DMXAA against colon 38 tumours in nude or thymectomized mice. Further, nonvascularized tumour tissue is relatively insensitive to FAA-induced killing in mice (Finlay et al, 1988;Zwi et al, 1989Zwi et al, , 1990, and a correlation has been demonstrated between blood flow inhibition by FAA and growth delay using a range of non-immunogenic mouse tumours (Hill et al, 1989). In the present study the effect of 5-HT on the anti-tumour effects of DMXAA was qualitatively similar for all three end points examined (blood flow inhibition at 4 h, necrosis at 12 h and growth delay to 3 x treatment size), although the magnitude of the dose-modifying effects (>3, 2.3 and 2.0 respectively) were not identical.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the latter view, growth inhibition of murine colon tumours (but not antivascular effects) is compromised by T-cell depletion (Pratesi et al, 1990;Bibby et al, 1991) although similar studies by Ching et al (1992) showed little loss of activity of either FAA or DMXAA against colon 38 tumours in nude or thymectomized mice. Further, nonvascularized tumour tissue is relatively insensitive to FAA-induced killing in mice (Finlay et al, 1988;Zwi et al, 1989Zwi et al, , 1990, and a correlation has been demonstrated between blood flow inhibition by FAA and growth delay using a range of non-immunogenic mouse tumours (Hill et al, 1989). In the present study the effect of 5-HT on the anti-tumour effects of DMXAA was qualitatively similar for all three end points examined (blood flow inhibition at 4 h, necrosis at 12 h and growth delay to 3 x treatment size), although the magnitude of the dose-modifying effects (>3, 2.3 and 2.0 respectively) were not identical.…”
Section: Discussionmentioning
confidence: 99%
“…The former type appeared to have accumulated over time, and the necrotic material furthest from the viable tissues showed the greatest degree of nuclear breakdown. Drug-induced necrososis was more uniform and less advanced, as described previously in spheroids (Zwi et al, 1990).…”
mentioning
confidence: 81%
“…The functional vessels of tumour and non-tumour tissues in untreated mice were demonstrated by fluorescence microscopy on frozen sections, as described previously (Zwi et al, 1990). Briefly, a single injection (0.0 Iml g' body weight) containing Hoechst 33342 (H33342) 3.25mM and 10-nonyl acridine orange (NAO) 2 mM in 5% w/v D-glucose and 4% dimethylsulphoxide, was given five minutes before killing and the tumours and normal tissues were excised, frozen and sectioned.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2 has also been linked with endothelial damage, possibly by the stimulation of endogenous lymphokine-activated killer (LAK) cells (Kotasek et al, 1988). 1989;Zwi et al, 1990) and has been suggested as the prototype anti-vascular agent (Denekamp, 1990 (Murray et al, 1987). The accumulating evidence of a vascular effect in different forms of cancer therapy, and the realisation that some agents may operate by an exclusively anti-vascular action, has prompted the suggestion that novel chemicals be tested for anti-vascular effects over and above routine screening for potential tumoricidal properties (Denekamp, 1990 (Denekamp, 1993).…”
Section: Anti-vascular Therapymentioning
confidence: 99%